Recurrent frames in true crime: comparative analysis of the Wanninkhof Case: Narrative Patterns in the Newspaper Story and the HBO Documentary 'Dolores' - Méndiz Noguero, Alfonso; Sánchez Esparza, Marta (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
The true crime genre experiences great popularity, especially on on-demand platforms. This study aims to identify recurring frameworks in media crime narratives by comparing press coverage with audiovisual true crime. To do so, it reviews the theoretical framework of framing applied to criminal journalistic narratives. Then, using an inductive method, it examines cases and documents available sources to compile reliable frameworks. Finally, this framework is applied to a relevant media event: the disappearance and murder of Rocío Wanninkhof. By contrasting journalistic coverage with HBO's 'Dolores. The Truth About the Wanninkhof Case', coinciding approaches emerge, intensified even in audiovisual narratives. True crime allows for the redemption of the villain, reshaping initial journalistic narratives through elaborated context and changes in the narrator, influencing the entire narrative construction.